CONQUERING THE AMBIGUITY OF OPTIC ATROPHY IN NORMAL TENSION GLAUCOMA: FROM MYSTERY TO MASTERY: Poster Presentation - Case Report - Resident - Nurwasis; Hakim, Affannul; Komaratih, Evelyn; Primitasari, Yulia (Majalah Oftalmologi Indonesia, 2023)
Introduction : The dilemma in diagnosing glaucoma often arises when optic atrophy is found alongside nonspecific glaucomatous findings and normal intraocular pressure (IOP), particularly in cases of normal tension glaucoma (NTG). This gray zone often leads to doubt and misdiagnosis. Case Illustration : A 70-year-old man previously diagnosed with idiopathic bilateral optic atrophy complained of blurred vision in both eyes. The visual acuity was 5/5 in the right eye (RE) and hand movement in the left eye (LE). Both eyes had normal IOP, open angles with Sampaolesi lines on gonioscopy, fibrin deposits at pupillary margins, and a large cup-to-disc ratio with baring and peripapillary atrophy on funduscopy. The OCT examination revealed thinning in the ONH-RNFL, ILM-RPE, and GCL-IPL complexes. HFA revealed tunnel vision in RE and general depression in LE. The patient was suspected of having NTG. We performed BMO-MRW (less than 100 ?m in both eyes) and 24-hour ocular perfusion pressure (OPP) measurements (less than 50 mmHg at night) to support the diagnosis. Discussion : The BMO-MRW examination is a new parameter that can help establish the diagnosis of glaucoma. A thin BMO-MRW finding suggests that optic atrophy originates from glaucoma. It is important to perform a comprehensive examination in cases of NTG to identify risk factors and prevent the development of glaucoma. Decreased OPP to less than 50 mmHg and PEX syndrome may be risk factors for NTG. Conclusion : In cases of doubtful optical atrophy, it is important to consider the possibility of NTG by performing a comprehensive examination, including BMO-MRW and twenty-four hour OPP measurements.